De‐centring Land Grabbing: Southeast Asia Perspectives on Agrarian‐Environmental Transformations Peter Vandergeest and Laura Schoenberger (eds.) Routledge, Abingdon, UK, 2018, pp. xi + 280 (ISBN 978‐0 ‐ 815 ‐ 35387 ‐ 4) hbk. - Kenney-Lazar, Miles (Wiley, 2019)
10.1111/sjtg.12282